Increasing Culturally Responsive Behavior among Graduate Students Preparing for Careers with Neurodiverse Clients. - Tereshko, Lisa M.; Conners, Brian; Weiss, Mary Jane (Behavior & Social Issues, 2024)
The field of behavior analysis is continually evolving and there has been a call to action for increased culturally responsive interventions and practices by behavior analysts. Although the field is progressing in the discussion of culturally responsive practices, there continues to be limited progress in extending the training and development of behavior analytic professionals in this essential area. The current study describes a pilot intervention to build cultural responsiveness practices for behavior analytic professionals in a graduate course. The study sought to be an initial investigation in determining whether the integration of a culturally responsive training package would increase the cultural responsiveness of graduate students in a behavior analysis program. Participants had an increase in self-assessment scores across phases and statistically significant increases in culturally responsive replies to various cultural scenarios upon the introduction of both phases of intervention. Implications, limitations, and future directions, especially for teaching and training members of the behavior analytic profession, are discussed.